Pathogenic mechanisms in prion disease - Mallucci, Giovanna (Henry Stewart Talks, 2014)
Neurodegenerative diseases and protein misfolding disorders, Prion disease in mice to study mechanisms of neurodegeneration due to misfolded protein accumulation, Early prion neurodegenerative change is reversible: access to key neurotoxic pathways, Critical change is loss of synaptic proteins due to activation of PERK branch of the unfolded protein response, Modifying this pathway genetically is neuroprotective, Modifying this pathway pharmacologically is neuroprotective, Relevance of this pathway in other neurodegenerative diseases with misolded proteins e.g. Alzheimer’s and Parkinson’s and ALS, Relevance in learning and memory, Common target for therapy in these disorders